Microbes and Viruses Are Bugging the Gut in Celiac Disease. Are They Friends or Foes? - Lerner, Aaron; Arleevskaya, Marina; Schmiedl, Andreas; Matthias, Torsten (Frontiers in Microbiology, 2017)
The links between microorganisms/viruses and autoimmunity are complex and multidirectional. A huge number of studies demonstrated the triggering impact of microbes and viruses as the major environmental factors on the autoimmune and inflammatory diseases. However, growing evidences suggest that infectious agents can also play a protective role or even abrogate these processes. This protective crosstalk between microbes/viruses and us might represent a mutual beneficial equilibrium relationship between two cohabiting ecosystems. The protective pathways might involve post-translational modification of proteins, decreased intestinal permeability, Th1 to Th2 immune shift, induction of apoptosis, auto-aggressive cells relocation from the target organ, immunosuppressive extracellular vesicles and down regulation of auto-reactive cells by the microbial derived proteins. Our analysis demonstrates that the interaction of the microorganisms/viruses and celiac disease (CD) is always a set of multidirectional processes. A deeper inquiry into the CD interplay with Herpes viruses and Helicobacter pylori demonstrates that the role of these infections, suggested to be potential CD protectors, is not as controversial as for the other infectious agents. The outcome of these interactions might be due to a balance between these multidirectional processes.